1995
DOI: 10.1002/jms.1190300604
|View full text |Cite
|
Sign up to set email alerts
|

Collisional activation spectra of organic ions

Abstract: Col&sion with neutral molecules is shown to provide a convenient method of adding internal energy to ions in a field-free drift region of the mass spectrometer. The effects on this process of ion accelerating potential, target gas pressure and identity, and precursor ion internal energy and mass have been investigated to optimize experimental conditions. Such collisions cause ion decompositions whose activation energies cover a broad range; for a particular ion such decompositions can be viewed as its "collisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 1 publication
(1 reference statement)
0
14
0
1
Order By: Relevance
“…The transfer through the capillary took about 15 s; further 30 -60 s were necessary to allow for evaporation of the solvent and for further pumping to recover the ion source vacuum. To ensure smooth operation without discharges, the pressure inside the ion source housing was allowed to fall to at least 8 ϫ 10 Linked scans at constant B/E [44] were employed to acquire the first field-free region metastable ion or collision-induced dissociation (CID) [45,46] spectra of the selected precursor ions. For CID measurements helium was used as collision gas.…”
Section: Methodsmentioning
confidence: 99%
“…The transfer through the capillary took about 15 s; further 30 -60 s were necessary to allow for evaporation of the solvent and for further pumping to recover the ion source vacuum. To ensure smooth operation without discharges, the pressure inside the ion source housing was allowed to fall to at least 8 ϫ 10 Linked scans at constant B/E [44] were employed to acquire the first field-free region metastable ion or collision-induced dissociation (CID) [45,46] spectra of the selected precursor ions. For CID measurements helium was used as collision gas.…”
Section: Methodsmentioning
confidence: 99%
“…From these studies, it was concluded that the nature of the collision gas has little influence on the product fragment intensity ratios [16,17]. Though, in recent studies with other molecules, the nature of the collision gas was observed to influence the fragmentation [18][19][20].…”
Section: Introductionmentioning
confidence: 97%
“…In the late 1960s and early 1970s, McLafferty and co-workers performed in-depth studies of keV collisional activation fragmentation as a function of various parameters [16]. From these studies, it was concluded that the nature of the collision gas has little influence on the product fragment intensity ratios [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…C ollision-induced dissociation (CID) is the most commonly employed method for structural elucidation of various compounds ranging from small organic molecules to large biomolecules in mass spectrometry [1,2]. CID is usually accomplished by ion activation with electric fields and then ion energetic collisions with a neutral gas followed by chemical bond dissociation and ion fragmentation [3].…”
Section: Introductionmentioning
confidence: 99%